2022
DOI: 10.1111/dom.14776
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glucagon‐like peptide 1 receptor agonists on albuminuria in adult patients with type 2 diabetes mellitus: A systematic review and meta‐analysis

Abstract: Aims To determine the effect of glucagon‐like peptide 1 receptor agonists (GLP‐1RAs) on albuminuria in adult patients with type 2 diabetes mellitus (T2DM). Methods Medline Ovid, Scopus, Web of Science, EMCARE and CINAHL databases from database inception until 27 January 2022. Studies were eligible for inclusion if they were randomized controlled trials that involved treatment with a GLP‐1RA in adult patients with T2DM and assessed the effect on albuminuria in each treatment arm. Data extraction was conducted i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 70 publications
(171 reference statements)
0
7
0
Order By: Relevance
“…Of importance, this amelioration of the risk for CKD progression has been shown to be mainly driven by the achieved reduction in albuminuria levels 41 . GLP‐1RA treatment in T2DM has also been associated with a significant decrease in albuminuria levels, compared with control, according to a relevant, recent meta‐analysis, although the absolute numeric change seems to be inferior to that achieved with SGLT2 inhibitors and tirzepatide 42 . In total, both antidiabetic drug classes ameliorate albuminuria and decrease the risk for CKD progression in T2DM 43 ; however, SGLT2 inhibitors might be superior to GLP‐1RAs for renal outcomes in patients with T2DM, regardless of albuminuria status at baseline 44 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of importance, this amelioration of the risk for CKD progression has been shown to be mainly driven by the achieved reduction in albuminuria levels 41 . GLP‐1RA treatment in T2DM has also been associated with a significant decrease in albuminuria levels, compared with control, according to a relevant, recent meta‐analysis, although the absolute numeric change seems to be inferior to that achieved with SGLT2 inhibitors and tirzepatide 42 . In total, both antidiabetic drug classes ameliorate albuminuria and decrease the risk for CKD progression in T2DM 43 ; however, SGLT2 inhibitors might be superior to GLP‐1RAs for renal outcomes in patients with T2DM, regardless of albuminuria status at baseline 44 …”
Section: Discussionmentioning
confidence: 99%
“…41 GLP-1RA treatment in T2DM has also been associated with a significant decrease in albuminuria levels, compared with control, according to a relevant, recent meta-analysis, although the absolute numeric change seems to be inferior to that achieved with SGLT2 inhibitors and tirzepatide. 42 In total, both antidiabetic drug classes ameliorate albuminuria and decrease the risk for CKD progression in T2DM 43 ; however, SGLT2 inhibitors might be superior to GLP-1RAs for renal outcomes in patients with T2DM, regardless of albuminuria status at baseline. 44 Thus, tirzepatide seems to be a 'rising star' for the prevention and delaying of CKD and related, surrogate renal outcomes in patients with T2DM, despite the fact that, to date, there is no solid evidence, based on the absence of dedicated renal outcome trials.…”
Section: Discussionmentioning
confidence: 99%
“…Secondary analyses from the SUSTAIN-6 trial found that semaglutide reduced the risk of new onset or deterioration of chronic renal disease, as the composite outcome of persisting macroalbuminuria, doubling of serum creatinine, or end-stage renal disease was reduced by 36% [33]. The result of a systematic review and meta-analysis indicates that GLP-1RAs, compared to placebo, provide a statistically relevant improvement in albuminuria by around 16% [58].…”
Section: Tirzepatide and Renal Outcomesmentioning
confidence: 99%
“…Renally, GLP-1RAs seem to facilitate natriuresis and mitigate hyperfiltration [104]. According to a recent metaanalysis encompassing at least 22 published articles [106], the use of GLP-1RAs was linked to a noteworthy reduction (16.14%) in albuminuria in patients with type 2 diabetes mellitus compared to a placebo. A novel compound, tirzepatide, which acts as both a glucose-dependent insulinotropic polypeptide (GIP) receptor agonist and a GLP-1 RAs, exhibited a significant impact on decreasing albuminuria [107].…”
Section: Glucagon-like Peptide 1 Receptor Agonistmentioning
confidence: 99%